Interfirm Monitoring, Social Contracts, and Relationship Outcomes - Heide, Jan B.; Wathne, Kenneth H.; Rokkan, Aksel I. (Journal of Marketing Research, 2007)
This article examines the effects of monitoring on interfirm relationships. Whereas some research suggests that monitoring can serve as a control mechanism that reduces exchange partner opportunism, there is also evidence showing that monitoring can actually promote such behavior. The authors propose that the actual effect of monitoring depends on (1) the form of monitoring used (output versus behavior) and (2) the context in which monitoring takes place. With regard to the form of monitoring, the results from a longitudinal field study of buyer–supplier relationships show that output monitoring decreases partner opportunism, as transaction cost and agency theory predict, whereas behavior monitoring, which is a more obtrusive form of control, increases partner opportunism. With regard to the context, the authors find that informal relationship elements in the form of microlevel social contracts serve as buffers that both enhance the effects of output monitoring and permit behavior monitoring to suppress opportunism in the first place.